A perspective on increasing the efficiency of proton exchange membrane water electrolyzers– a review. (12th May 2023) - Makhsoos, Ashkan; Kandidayeni, Mohsen; Pollet, Bruno G.; Boulon, Loïc
Abstract: Decarbonized hydrogen production using renewable energy sources and water electrolysis is perceived as a promising solution for a sustainable future. The efficiency of PEMWEs relies on several multiphysical aspects and even a slight increase in their efficiency may change the future of sustainable energy routes. Hence, this paper reviews the most compelling research on increasing PEMWE efficiency, which is one of the main pillars for the advancement of this technology. Various publications, including chemical engineering, materials, mass transfer, energy transfer, electrical control, power generation, and hybrid systems, are considered. From the electrolyzer power sources (renewable energy, hybrid, power to gas), inputs (power regulation, water temperature, pressure, ambient temperature), and stack, to components design, control strategy, and new hybrid designs have come under scrutiny in this manuscript. Finally, five essential recommendations are given as the pathways for future studies on PEMWE efficiency.